2017
DOI: 10.3917/cips.112.0477
|View full text |Cite
|
Sign up to set email alerts
|

Représentation sociale de l’autisme

Abstract: Cette recherche a pour but d’étudier la représentation sociale de l’autisme ainsi que l’effet du contact sur cette représentation. Nous avons procédé à un recueil de données via association libre à partir du mot inducteur « autisme ». Le corpus a fait l’objet d’analyses prototypique, catégorielle et de similitude. Les résultats confirment l’existence d’une représentation sociale de l’autisme. Nous observerons également des similitudes entre les contenus des représentations sociales des deux sous-populations, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Some are associated with intellectual difficulties and challenging behaviors, while some others are not. Nevertheless, independent of this diversity, the overall negative lay representation of autism seems to dominate (Dachez et al, 2016). This homogenization that lies at the core of stereotypical perceptions, especially toward ASD, can reinforce the less positive attitudes observed, while, on the contrary, introducing variability can have the opposite effects (Brauer and Er-rafiy, 2011;Jury et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some are associated with intellectual difficulties and challenging behaviors, while some others are not. Nevertheless, independent of this diversity, the overall negative lay representation of autism seems to dominate (Dachez et al, 2016). This homogenization that lies at the core of stereotypical perceptions, especially toward ASD, can reinforce the less positive attitudes observed, while, on the contrary, introducing variability can have the opposite effects (Brauer and Er-rafiy, 2011;Jury et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…As a consequence, the attitudes of participants could have been colored by their stereotypical beliefs regarding these specific disabilities. It has notably been shown that individuals with CD are perceived as particularly kind (Sadler et al, 2012) while individuals with ASD suffer from a generally negative social representation, since they can be perceived as having a "disease" that makes them "inaccessible" (Dachez et al, 2016; see also Rohmer and Louvet, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, the present findings revealed a weak difference, although significant, in terms of attitudes towards inclusive education for students with intellectual disabilities and those with autism spectrum disorder, both being the most negative ones in comparison with attitudes regarding other disabilities. Such a resemblance suggests that similar barriers, eventually resulting from existing negative stereotypes in terms of competence (Rohmer & Louvet, 2011) but also behaviours (Dachez et al, 2016) can contribute to explain the exclusion that students with autism spectrum disorder could face within the mainstream educational system (Rattaz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…No início, na França, a Teoria das Representações Sociais (TRS) já era utilizada em áreas de interface da psicologia social, sobretudo a da saúde (HERZLICH, 1984;JODELET, 1989). Mesmo hoje, ela continua sendo empregada no contexto aplicado da saúde, sobretudo da saúde coletiva (JODELET, 2014;DACHEZ, N'DOBO, CARRASCAL, 2016;COHEN, MOLINER, 2017).…”
unclassified